2010
DOI: 10.1073/pnas.1009483107
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent gallbladder carcinogenesis in LXRβ −/− female mice

Abstract: Gallbladder cancer is a highly aggressive disease with poor prognosis that is two to six times more frequent in women than men. The development of gallbladder cancer occurs over a long time (more than 15 y) and evolves from chronic inflammation to dysplasia/metaplasia, carcinoma in situ, and invasive carcinoma. In the present study we found that, in female mice in which the oxysterol receptor liver X receptor-β (LXRβ) has been inactivated, preneoplastic lesions of the gallbladder developed and evolved to cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 49 publications
2
37
1
Order By: Relevance
“…Therefore, exploring new treatment targets for GBC is an urgent matter at present. Epidemiological studies displayed that incidence of GBC exhibited distinct gender biasness, which affected females two to three times than males (Lazcano-Ponce et al, 2001;Gabbi et al, 2010). This gender predominance indicated that estrogen may be a possible promoter of carcinogenesis in gallbladder.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring new treatment targets for GBC is an urgent matter at present. Epidemiological studies displayed that incidence of GBC exhibited distinct gender biasness, which affected females two to three times than males (Lazcano-Ponce et al, 2001;Gabbi et al, 2010). This gender predominance indicated that estrogen may be a possible promoter of carcinogenesis in gallbladder.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, female sex hormones adversely influence hepatic bile secretion and gallbladder function [39]. Estrogens increase cholesterol secretion and diminish bile salt secretion, while progestins act by reducing bile salt secretion and impairing gallbladder emptying leading to stasis [40]. These may partially explain the stronger association observed with overweight or obesity in women than in men.…”
Section: Discussionmentioning
confidence: 49%
“…Most of the cases of this tumor are females. In addition, ovariectomized estrogen-free LXRβ -/-mice failed to develop preneoplastic lesions 3 . These observations suggest role of estrogen in gallbladder carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%